2019
DOI: 10.1016/j.neurobiolaging.2018.10.018
|View full text |Cite
|
Sign up to set email alerts
|

High-fat diet worsens the impact of aging on microglial function and morphology in a region-specific manner

Abstract: Hippocampal microglia are vulnerable to the effects of ageing, displaying a primed phenotype and hyper-responsiveness to various stimuli. We have previously shown that short-term high fat diet (HFD) significantly impairs hippocampal-and amygdala-based cognitive function in the aged without affecting it in the young. Here we assessed if morphological and functional changes in microglia might be responsible for this. We analysed hippocampus and amygdala from young and ageing rats that had been given three days H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 67 publications
(82 reference statements)
2
31
0
Order By: Relevance
“…Proliferation of microglia might also depend on the age of HFD exposure. Aged animals appear to be more susceptible to develop HFD-induced neuroinflammation (Spencer et al, 2019). Hsu et al (2015) also observed age-dependent inflammation effects of exposure to sugar-rich diets.…”
Section: Inflammation and Gliosismentioning
confidence: 94%
“…Proliferation of microglia might also depend on the age of HFD exposure. Aged animals appear to be more susceptible to develop HFD-induced neuroinflammation (Spencer et al, 2019). Hsu et al (2015) also observed age-dependent inflammation effects of exposure to sugar-rich diets.…”
Section: Inflammation and Gliosismentioning
confidence: 94%
“…For morphology in the 7and 14-day groups, all cells were categorized as ameboid (0-1 primary process), intermediate (2-4 primary processes), or ramified (five or more primary processes). We also assessed microglial complexity with a Sholl analysis on three cells per section from the same images as described in detail in [28]. Data were grouped into bins of 1-10 or 1-20 μm for analysis with repeated measures analyses of variance (ANOVA) followed, where significant, by Student's unpaired t tests.…”
Section: Microglia Astrocyte and Neuronal Assessmentmentioning
confidence: 99%
“…While we focused on the HT because it is a well-known area involved in energy balance regulation (Gao & Horvath, 2008), we do not exclude the possibility that other brain areas may also display postprandial inflammation associated with neuropeptide modulation. Indeed, several studies have shown that chronic HFD consumption leads to hippocampal inflammatory responses and affects behavioral disorders associated with obesity (Abbink, van Deijk, Heine, Verheijen, & Korosi, 2019;Guillemot-Legris et al, 2016;Gzielo, Kielbinski et al 2017;Spencer, Basri et al 2019;Tsai, Wu et al 2018;Waise et al, 2015). Moreover, astrocytes in the brainstem dorsal vagal complex responds to acute nutritional excess (MacDonald et al, 2020).…”
Section: F I G U R Ementioning
confidence: 99%